The effectiveness of using songs in teaching english langauge as a didactic method to help children from kindergarten to learn vocabulary at Antonio Jose de Sucre elementary school, in David City 2009 - Lezcano Samudio, Ingrid Magalys (UDELAS, 2010)
The importance of this studyl begins by stablishing whether a study guide, a practical approach of learning the english language, and the use of songs in the target language are effective didactic resources that provides a better acquisicition of a second language in children of this age.